The Letters of Kadmos: Mythology, Archaeology and Eteocretan - Stieglitz, R. R. (1981)
Ugaritic alphabetic cuneiform letters on the bases of Mycenaean vases from the Levant, cf. Newsletter Ug. 29 (1983) 3.